The Implications of Screentime for Children’s Health in Online Learning at 59 Siguntu Elementary School, Palopo City - Santi; Herawati Ramli; Sumiati (Jurnal Life Birth, 2022)
As a result of too long screen time, it could make students sluggish, obesity and various non-communicable diseases, as well as risks related to eye health and social emotional development. This study aimed to systematically identify the impact of the screen time on students’ health in online learning. The research used qualitative research methods through a phenomenological approach. Data collected with focus group discussions (FGD) and in-depth interviews. FGD were conducted on 10 students. In-depth interviews were carried out on ten key informants, students in grades III to VI that constantly utilize cellphones, five ordinary informants, which were students’ parents. The results showed that the impact of screen time on students in physical healths are ocular fatigue, itchy, sore and stiffed hands while using or holding the gadget screen for too long, but from a social perspective, it is not so influential because students tend to prefer playing with school friends compared to playing gadgets at home. In terms of implications for student behavior, there are some affections on their health, as if their irregular sleep time at night due to watching shows or movies that are considered fun, but in the term of the affective health, it has no significant effect by observing their actions are still as usual. Also, there are no showed frontal actions or habits that breaking the norm, and they can still enjoy playing time with their friends. Based on the results of the research obtained, it concluded that the implications of screen time on students’ health can be reduced or prevented by leading the student’s learning to be more active in field activities like playing with their friends, so the tendency to play on cellphones can be reduced and bring over to prevent the bad affections of screen time on students’ health in SD 59 Siguntu. Therefore, the growth and development of the students can be optimized without any disturbances that must be faced during their development.